In Search of Larger Per Capita Incomes: How To Prioritize across Productivity Determinants? - Alejandro Izquierdo; Jimena Llopis; Umberto Muratori; José Juan Ruiz (Inter-American Development Bank (IDB), 2016)
This study is a first contribution to prioritization across productivity determinant capabilities that attempts to obtain the equivalent of a "shadow price" for each of these capabilities by estimating their impact on the success a country may have in reaching higher income per capita groups. The prioritization of these determinants-spanning different sectors-seems to be specific to the income per capita group to which a country belongs. Moreover, empirical estimates reveal that interactions among sectors matter for increasing the probability of climbing up the income-per-capita ladder, reflecting the existence of complementarities across sectors, thus indicating that the joint improvement of some of them may be necessary before effects are noticeable. Results also indicate that the identification of priorities by looking at the impact that sectors have on increasing the likelihood of advancing to a better income per capita group may or may not coincide with the size of sector gaps typically used for the determination of priorities, as larger gaps do not necessarily capture the relevance of sectoral restrictions and their interactions.
hdl:11319/7511
Keywords: O10; O40; O47; 330; Development; Productivity; Per capita income priorities; Growth